Can forward guidance be ambiguous yet effective? - Danvee Floro; Mewael F. Tesfaselassie (Kiel Institute for the World Economy (IfW), 2013)
[Concluding remarks] The financial crisis has rendered conventional monetary policy (of major central banks) powerless. Unconventional monetary policy, in the form of forward guidance and quantitative easing, has taken center stage. Recent moves in financial markets have challenged the notion that forward guidance can be separated from the unwinding of quantitative easing and also shown that forward guidance can have perverse effects on market expectations. Nonetheless, forward guidance, as is currently formulated in practice, may be ineffective in managing market expectations not because central banks are powerless, but because they are too cautious, resulting in ambiguity in policy communication. Vagueness in communication is manifested by the insertion of conditionality and/or by the expression of intent, belief etc., to maintain accommodative policy on a certain course. Setting aside whether caution is warranted or not, the fact is that such vagueness is driven mainly by central banks' unwavering commitment to price stability, a commitment which is credible owing to their hard-won reputation. Financial markets are aware of this commitment. Saying that, the remark in January 2000 by Ben Bernanke that 'far from being powerless, the Bank of Japan could achieve a great deal if it were willing to abandon its excessive caution,' is still relevant now, as it was back then.
Keywords: 330